Lower Energy Storage-Based 9L- Switched Capacitor ANPC Inverter Topology With Voltage Boosting Features - R. Sekar; M. Jagabar Sathik; Mamdouh L. Alghaythi; Meshari S. Alshammari; K. Vijayakumar (IEEE Access)
This article proposes a novel 9L-switched capacitor inverter circuit with a voltage-boosting feature. The presented circuit uses fewer energy-stored capacitors, which reduces the size and cost. The conventional Active Neutral Point Clamped (ANPC) inverter output voltage is half of the input voltage, i.e. dc-link voltage requirement is double the output voltage which leads to several challenges such as high dc-link capacitor size and voltage ratings, front-end DC-DC boost converter, etc. These issues are eliminated in the proposed topology due to boosting features, but a soft-charging method is required to suppress the inrush current. A detailed comparison between the proposed and existing SC-based 9L- inverter is presented. To validate the proposed circuit, the simulation is carried out using MATLAB/Simulink tool and the same is verified in a prototype setup for 0.8 kW and its efficiency is 97.02% which is superior than the other topologies relating to this research work.